2020
DOI: 10.3389/fncel.2020.565841
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Mediated Homeostatic Synaptic Plasticity: From in vitro to in vivo Models

Abstract: Since it was first described almost 30 years ago, homeostatic synaptic plasticity (HSP) has been hypothesized to play a key role in maintaining neuronal circuit function in both developing and adult animals. While well characterized in vitro, determining the in vivo roles of this form of plasticity remains challenging. Since the discovery that the pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) mediates some forms of HSP, it has been possible to probe some of the in vivo contribution of TNF-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 116 publications
3
60
1
Order By: Relevance
“…Cytokines such as CXCL10 and TNF, that were found to be upregulated in the pathway analysis are secreted by microglia and exert several downstream effects not only on immune regulation, but also, in the case of TNF, on synaptic plasticity, neurogenesis and astrocyte function 51 . For example, it has been shown that TNF changes AMPA receptor current 52 similar to what we saw in our earlier work 26 . TNF is also an important molecule in cellular immunity, in particular T cell function 53 and it is no surprise that we found it to be the most activated gene for the causal network.…”
Section: Discussionsupporting
confidence: 87%
“…Cytokines such as CXCL10 and TNF, that were found to be upregulated in the pathway analysis are secreted by microglia and exert several downstream effects not only on immune regulation, but also, in the case of TNF, on synaptic plasticity, neurogenesis and astrocyte function 51 . For example, it has been shown that TNF changes AMPA receptor current 52 similar to what we saw in our earlier work 26 . TNF is also an important molecule in cellular immunity, in particular T cell function 53 and it is no surprise that we found it to be the most activated gene for the causal network.…”
Section: Discussionsupporting
confidence: 87%
“…Age-dependent decline in dopamine-dependent cognition and movement is observed in humans [55][56][57]70 , non-human primates 71 , and rodents 40,60 , supporting the idea of perturbed synaptic function within this circuitry. The cytokines we find to be elevated within the VTA, TNFα and IL-1β, have both been shown to influence key aspects of glutamatergic and GABAergic synapse receptor composition, function, and placticity 72,73 . Finally, lifestyle manipulations that alter microglial phenotype and reduce inflammation, are correlated with improved cognition during aging 74,75 .…”
Section: Chronic Local Inflammation As One Consequence Of Microglial Proliferation During Aging?mentioning
confidence: 70%
“…Lifestyle manipulations such as exercise and low-fat diet that alter microglial phenotype and reduce inflammation are also associated with improved cognition 73 . Moreover, microglial TNFα has been shown to influence presynaptic probability of release and insertion/removal of postsynaptic AMPA receptors at glutamatergic synapses 83 . TNFα can also impact GABA receptor insertion/removal from inhibitory synapse, placing this molecule in a position to influence the overall balance of excitatory and inhibitory input to neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TNF-α activates glutamatergic synaptic transmission by increasing presynaptic activity, postsynaptic AMPAR trafficking and synaptic insertion, while at the same time, suppressing inhibitory synaptic transmission [ 41 , 125 ]. Further, TNF-α has been implicated in homeostatic (non-Hebbian) synaptic scaling, through its ability to regulate the quantity of synaptic AMPA receptors, as well as by synaptic pruning by controlling the phagocytosis capacity of microglia [ 47 , 125 ]. Similarly, the multi-protein complex, called the inflammasome, that controls the secretion of the pro-inflammatory cytokines, IL-1β and IL-18, is also thought to regulate synaptic pruning and play a role in neuronal survival [ 134 ].…”
Section: Main Textmentioning
confidence: 99%